TINJAUAN YURIDIS RATIO DECIDENDI HAKIM DALAM MEMBERIKAN PIDANA MATI KEPADA PELAKU RUDAPAKSA (Studi Putusan Nomor 86/Pid.Sus/2022/PT Bdg) - Sanjaya, Made Dharmayoga; Perbawa, Ketut Sukawati Lanang (Jurnal Hukum Mahasiswa, 2024)
A crime that often occurs in Indonesia is rape or rudapaksa. One of the cases of rudapaksa was carried out by Herry Wirawan against 12 underage students as victims. Because of his actions, he was sentenced to death by the judge. This study uses normative methods with primary and secondary sources of legal materials, as well as legislative approaches and cases that are analyzed using analytical descriptive methods. The results of the study show that the legal basis for the regulation of the death penalty in Indonesia is regulated in positive law, including in the Criminal Code and outside the Criminal Code, as well as the Constitutional Court's decision that states that the death penalty is constitutional. Furthermore, the judge's ratio decidendi in imposing the death penalty against the perpetrator of rudapaksa in the Bandung High Court Decision Number: Number 86/Pid.Sus/2022/PT Bdg is based on juridical, philosophical, and sociological considerations, as well as the fact that the defendant's actions are not only unlawful, but also have a serious impact on the victim and society.